Motivational Factors in the Research Competencies of Nursing Students - Midelayde Vitor Tolentino, Carmen (2022)
This research aimed to determine the relationship between motivational factors and investigative skills in nursing interns from a university degree program. It was a study of the hypothetical-deductive method, with a quantitative approach, of a basic type, of a non-experimental, descriptive, correlational design; there was a universe population of 236 nursing interns from a private university. The survey technique was applied for both variables, in addition there were 2 Likert-type questionnaires that were validated by 5 expert judges and with an Aiken V of a value of 1 being valid, and with a Cronbach’s alpha of 0.928 for motivational factors and 0.988 for investigative skills. Therefore, they are reliable. The results indicated that the majority presented a high level of motivational factors with 59.2% (71) and with a high level of investigative skills with 87.5% (105); with a correlation of variables by Spearman’s Rho of Rho value = .944 and P = 0.003 between the variable’s motivational factors and investigative skills. It was concluded that there is a high significant positive correlation.